The role of social entrepreneurship in achieving United Nations’ sustainable development goals : Case Costa Rica - Häsänen, Ilona (My University, 2019)
Our Mother Earth is in crisis. In order deal that crisis, United Nation’s created the Agenda 2030 which includes 17 sustainable developments goals (SDGs) regarding issues like poverty, hunger, responsible consumption and production and climate change. Costa Rica was the first country in the world to sign a national pact for the SDGs. Nevertheless, many individuals, like social entrepreneurs, are getting frustrated and they do not want to wait for the governments to take the lead but act themselves for a better future. Consequently, the main research question in this master thesis is what is the role of social entrepreneurship in achieving United Nations’ sustainable development goals in Costa Rica? The sub-questions for this study are: · What kind of social enterprises are there in Costa Rica? · Which SDGs are tackled by social enterprises in Costa Rica? · Which dimensions of sustainable development are covered by social enterprises in Costa Rica? The research was conducted with qualitative methods. Primary data was collected by interviewing three social entrepreneurship experts and secondary data was collected from the internet. The selected 17 social enterprises in Costa Rica tackled 12 of the 17 SDGs. Some social enterprises tackled multiple SDGs at once and in many SDG, there was more than one social enterprise. The 17 social enterprises covered all the sustainable development dimensions. Social enterprises are a major force in enforcing sustainable development. Although, Costa Rican government has made progress, the data of this study indicates that social enterprises can help in the process. Social entrepreneurship is how business should be done and often social enetrprises try to fill the gaps that other sectors leave behind. Social enterprises can surely help to achieve the SDGs but not alone. Individuals, enterprises, non-profits and governments all must participate. Everyone must do their best in order to achieve the SDGs by 2030, also you and me.
Keywords: Social entrepreneurship, sustainable development, UN, SDGs, Costa Rica, yhteiskunnallinen yrittäjyys, YK, kestävän kehityksen tavoitteet, Costa Rica